Correction: Synthesis and optical properties of lead-free cesium germanium halide perovskite quantum rods. Issue 58 (21st October 2019) - Chen, Lin-Jer
Abstract : Correction for 'Synthesis and optical properties of lead-free cesium germanium halide perovskite quantum rods' by Lin-Jer Chen, RSC Adv., 2018, 8, 18396–18399.